2009
DOI: 10.1103/physreva.80.062105
|View full text |Cite
|
Sign up to set email alerts
|

Pair creation rates for one-dimensional fermionic and bosonic vacua

Abstract: We compare the creation rates for particle-antiparticle pairs produced by a supercritical force field for fermionic and bosonic model systems. The rates obtained from the Dirac and Klein-Gordon equations can be computed directly from the quantum-mechanical transmission coefficients describing the scattering of an incoming particle with the supercritical potential barrier. We provide a unified framework that shows that the bosonic rates can exceed the fermionic ones, as one could expect from the Pauli-exclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 48 publications
4
33
0
Order By: Relevance
“…Studies of spin effects in pair production by a high-energy photon and a strong laser field were performed in Tsai, 1993 andIvanov et al, 2005, based on considerations on helicity amplitudes and on the spinpolarization vector, respectively. Characteristic differences between fermionic and bosonic particles have been revealed with respect to pair creation in an oscillating electric field and in recent studies of the Klein paradox (Cheng et al, 2009b;Krekora et al, 2004;Wagner et al, 2010a). In the latter case it was shown that the existence of a fermionic (bosonic) particle in the initial state leads to suppression (enhancement) of the pair production probability due to the different quantum statistics.…”
Section: Spin Effects and Other Fundamental Aspects Of Laser-inducmentioning
confidence: 99%
“…Studies of spin effects in pair production by a high-energy photon and a strong laser field were performed in Tsai, 1993 andIvanov et al, 2005, based on considerations on helicity amplitudes and on the spinpolarization vector, respectively. Characteristic differences between fermionic and bosonic particles have been revealed with respect to pair creation in an oscillating electric field and in recent studies of the Klein paradox (Cheng et al, 2009b;Krekora et al, 2004;Wagner et al, 2010a). In the latter case it was shown that the existence of a fermionic (bosonic) particle in the initial state leads to suppression (enhancement) of the pair production probability due to the different quantum statistics.…”
Section: Spin Effects and Other Fundamental Aspects Of Laser-inducmentioning
confidence: 99%
“…for fermions (T F ) and bosons (T B ), respectively [27]. Here p(E) and q(E) are the momenta of the particles at a point where V (x) = 0 and V (x) = V 0 and are equal to…”
Section: B the Pair-creation Rate For The Time-independent Potentialsmentioning
confidence: 99%
“…This model is very simple but it contains the main physical features required to understand the variations in the pair production rate. Other 1-D models have been considered in the literature [21,29,20,30] while an analytical approach to the relativistic ionization of a 3D two-center system can be found in [31]. This article is organized as follows.…”
Section: Introductionmentioning
confidence: 99%